Exploring the ins and outs of biodiversity in the moral community. (May 2020) - Batavia, Chelsea; Bruskotter, Jeremy T.; Jones, Julia A.; Nelson, Michael Paul
Abstract: If moral concern for nonhuman nature underpins conservation, it is essential to understand how individuals populate their "moral communities, " a core concept from environmental ethics, with various elements of biodiversity. Using data from an online survey of the United States public ( N  = 1331), we investigated the extent to which respondents' moral communities align with four worldviews discussed in the environmental ethics literature: anthropocentrism, zoocentrism, biocentrism, and ecocentrism. Each worldview provides a vision for how the moral community should be constituted. To assess inclusion in terms consistent with ethical theory, we measured whether and the extent to which respondents included abstract sets of entities (humans, sentient/subjective entities, living organisms, entities with vital interests). To assess inclusion in terms relevant to conservation, we measured whether and the extent to which respondents included specific kinds of entities within those sets (e.g., Americans, cougar, fungus, rainforest ecosystem). Roughly half the sample could be affiliated with anthropocentrism, zoocentrism, biocentrism, or ecocentrism, but these respondents did not always include the specific entities they were expected to include based on ethical theory. However, respondents with more inclusive worldviews did believe more entities are included in the moral community, and also professed those beliefs more strongly than respondents with less inclusive worldviews. If strength of inclusivity beliefs is associated with other pro-conservation attitudes, intentions, and behaviors, then people with larger, more diverse moral communities may more strongly support biodiversity conservation. Highlights: Society's moral community must include biodiversity for enduring conservation success. It is important to empirically understand the ethical concept of "moral community". ~50% of sample (N = 1331) align with four ethical views of moral community (worldviews). Respondents do not include all specific nonhuman entities predicted by ethical theory. Respondents with larger moral communities also report stronger inclusivity beliefs.